Signal transducer and activator of transcription (STAT)-3 regulates microRNA gene expression in chronic lymphocytic leukemia cells - Rozovski, Uri (BioMed Central, 2013)
BACKGROUNDS: Approximately 1,000 microRNAs (miRs) are present in the human genome; however, little is known about the regulation of miR transcription. Because miR levels are deregulated in chronic lymphocytic leukemia (CLL) and signal transducer and activator of transcription (STAT)-3 is constitutively activated in CLL, we sought to determine whether STAT3 affects the transcription of miR genes in CLL cells. METHODS: We used publically available data from the ENCODE project to identify putative STAT3 binding sites in the promoters of miR genes. Then we transfected CLL cells with STAT3-shRNA or with an empty vector, and to determine which miRs are differentially expressed, we used a miR microarray approach followed by validation of the microarray results for 6 miRs using quantitative real-time polymerase chain reaction (qRT-PCR). RESULTS: We identified putative STAT3 binding sites in 160 promoter regions of 200 miRs, including miR-21, miR-29, and miR-155, whose levels have been reported to be upregulated in CLL. Levels of 72 miRs were downregulated (n = 63) or upregulated (n = 9). qRT-PCR confirmed the array data in 5 of 6 miRs. CONCLUSIONS: The presence of activated STAT3 has a profound effect on miR expression in CLL cells.